Optimal planning of hybrid power systems under economic variables and different climatic regions: A case study of Türkiye - Ozturk, Zafer; Terkes, Musa; Demirci, Alpaslan (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Renewable energy-based hybrid power systems (HPS), proposed based on demand in the transition to clean energy-indexed societies, are high-potential investments. However, cost-based optimal sizing and feasibility analyses are complicated due to unforeseen variables and do not guarantee a reliable and robust optimization framework. This study optimizes minimum-cost HPS planning for diverse loads across varied climates and economic conditions, providing holistic comparisons of technical, financial, and environmental viability. According to the analysis, fluctuating economic structure emphasizes that unsubsidized hybrid power system installations are inefficient, the severe imbalance between inflation and interest rates limits the benefits of hybrid power systems and creates an uncertain investment environment for stakeholders. The gradual increase in interest rates to limit inflation has created a more viable renewable energy investment environment, while payback periods are reduced to 7.21 years. Even under identical economic conditions, the renewable fraction of energy in regions with high solar potential can be up to 25 % higher than in regions with less potential. Moreover, payback periods can vary up to 6 years, depending on the variability in solar generation and load profiles. Considering the significant impact of economic uncertainty on HPS investments, optimization plans that reduce investment risks will be helpful to stakeholders.
Keywords: Different load profiles; Economic variables; Feasibility; Hybrid power system; Optimization; Photovoltaic; RENEWABLE ENERGY SYSTEM; OPTIMAL-DESIGN; RURAL ELECTRIFICATION; AREA; COMMUNITY; Science & Technology - Other Topics; Energy & Fuels